Participative Management of Administrator and Flow at Work of Teachers in School Under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya - Bumrungveth, Krongkon; Tiacharoen, Assit.Prof.Dr.Saisuda (Journal of Dhamma for Life, 2023)
The Purposes of this research were to determine 1) participative management of administrator in school under the secondary educational service area office Phra Nakhon Si Ayutthaya 2) flow at work of teachers in school under the secondary educational service area office Phra Nakhon Si Ayutthaya 3) the relationship between the participative management of administrator and flow at work of teachers in school under the secondary educational service area office Phra Nakhon Si Ayutthaya. The sample was 28 schools under the secondary educational service area office Phra Nakhon Si Ayutthaya. There were 4 respondents from each school consisted of a school director or acting school director, a deputy director or acting deputy director and two teachers, totally 112. The research instrument was a questionnaire about the participative management based on Santi Boonpirom and flow at work based on Bakker. The statistical used for analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson’s product-moment correlation coefficient. The findings of the research were as follow: The participative management of administrator in school under the secondary educational service area office Phra Nakhon Si Ayutthaya, as a whole and each aspect were at a high level, ranking from the highest to the lowest arithmetic mean; participative in action, participative in improving new ways of working, participative in acceptant the evaluating results, participative in evaluating and participative in thinking. The flow at work of teachers in school under the secondary educational service area office Phra Nakhon Si Ayutthaya as a whole was at a highest level, when considered in each aspect, there were 2 aspects rated at a highest level, ranking from the highest to the lowest arithmetic mean; work enjoyment and Intrinsic work motivation. The other aspect was at high level, it was absorption. The relationship between the participative management of administrator and flow at work of teachers in school under the secondary educational service area office Phra Nakhon Si Ayutthaya was found correlated in moderate level at 0.01 level of statistical significance which was positive correlated.